Encouragement, Patient Perseverance, Community, and Surprise: Four Entangled Lessons from my Advisor, Dr. Ajay Heble - Finley, Ben (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Ben Finley reflects on lessons learned from his PhD Supervisor Ajay Heble.